Association of N6-methyladenosine readers' genes variation and expression level with pulmonary tuberculosis - Li, Hong-Miao; Tang, Fei; Wang, Li-Jun; Huang, Qian; Pan, Hai-Feng; Zhang, Tian-Ping (Frontiers in Public Health, 2022)
N6-Methyladenosine (m6A) is associated with many biological processes and the development of multiple diseases. The aim of this study was to analyze the association of m6A readers' genes variation, as well as their expression levels, with pulmonary tuberculosis (PTB). A total of 11 single-nucleotide polymorphisms (SNPs) in m6A readers' genes (i.e., YTHDF1 rs6122103, rs6011668, YTHDF2 rs602345, rs3738067, YTHDF3 rs7464, rs12549833, YTHDC1 rs3813832, rs17592288, rs2293596, and YTHDC2 rs6594732, and rs2416282) were genotyped by SNPscan™ technique in 457 patients with PTB and 466 normal controls. The m6A readers' genes expression levels in peripheral blood mononuclear cells (PBMCs) from 78 patients with PTB and 86 normal controls were detected by quantitative real-time reverse transcription polymerase chain reaction (qRT-PCR). There was no significant association between all SNPs in YTHDF1, YTHDF2, YTHDF3, YTHDC1, and YTHDC2 genes and PTB susceptibility. The increased frequencies of YTHDF2 rs3738067 GG genotype and YTHDC1 rs3813832 CC genotype, C allele, were, respectively, found in PTB patients with hypoproteinemia and fever. YTHDC2 rs6594732 variant was significantly associated with drug-induced liver damage and sputum smear-positive, and the rs2416282 variant was significantly associated with fever in patients with PTB. Compared with controls, the YTHDF1, YTHDF2, YTHDF3, YTHDC1, and YTHDC2 mRNA levels were significantly decreased in PTB. Moreover, YTHDF1 level was negatively associated with erythrocyte sedimentation rate (ESR), and YTHDF3 and YTHDC1 levels were negatively related to alanine aminotransferase (ALT) in patients with PTB. Our results demonstrated that YTHDF1, YTHDF2, YTHDF3, YTHDC1, and YTHDC2 genes SNPs did not contribute to PTB susceptibility, while their decreased levels in patients with PTB suggested that these m6A readers might play significant roles in PTB.